Teachers’ Way Applying Integrated Learning Using Integrated Model With Creativity in Development Simple Aircraft as Central Theme - Tahmid Sabri (STKIP Singkawang, 2018)
his research is carried out in cycles (stages), with some step steps that are (1) The teacher makes the design of integrated learning; (2) Conducted observations by the researcher; (3) Reflection is done to see together the constraints experienced by teachers when designing; (4) Implementing subsequent actions as remedial measures for teacher inaccuracies in previous activities; (5) The next step of implementing the design that has been made; (6) Reflections on the inaccuracy in the implementation of learning (7) Take the next class action as a remedy for inaccuracy in the implementation. Then the findings of this study include (1) Distribution of time in learning, both in the design of learning and in the implementation of learning difficult for teachers to distribute it appropriately; (2) The correlation between concepts in the related field of study, is still awkward or not yet done by the teacher appropriately; (3) Drawing conclusions in learning. Teachers have difficulty directing the students to conclude from the concepts already discussed (4) The views of integrated learning teachers need to be applied in elementary schools, as they can capture some concepts from several fields of study at the same time (5) Students' view that learning in an integrated way not difficult even fun, only a small part that says difficult because not yet accustomed.